2017
DOI: 10.1016/j.lithos.2017.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Basalts and picrites from a plume-type ophiolite in the South Qilian Accretionary Belt, Qilian Orogen: Accretion of a Cambrian Oceanic Plateau?

Abstract: 'Basalts and picrites from a plume-type ophiolite in the South Qilian Accretionary Belt, Qilian Orogen : accretion of a Cambrian Oceanic Plateau? ', Lithos.,[278][279][280][281] Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 82 publications
1
62
0
Order By: Relevance
“…The numbers indicate the degree of crustal contamination. Data source: Cambrian picrite in the regional Yongjing terrane from Y. Zhang et al (); metamorphosed basaltic rocks from the Hualong Group from T. Wang et al (); Xiashitang intrusion from Z. Zhang (). The calculated parameters of Sr (ppm), 87 Sr/ 86 Sr ( i ) , Nd (ppm), and εNd ( t ) are 320, 0.716, 27 and −10.8 for the upper crust and 348, 0.709, 11 and −7.6 for the lower crust, respectively [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers indicate the degree of crustal contamination. Data source: Cambrian picrite in the regional Yongjing terrane from Y. Zhang et al (); metamorphosed basaltic rocks from the Hualong Group from T. Wang et al (); Xiashitang intrusion from Z. Zhang (). The calculated parameters of Sr (ppm), 87 Sr/ 86 Sr ( i ) , Nd (ppm), and εNd ( t ) are 320, 0.716, 27 and −10.8 for the upper crust and 348, 0.709, 11 and −7.6 for the lower crust, respectively [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…The extent of crustal contamination can be estimated using εNd ( t ) versus 87 Sr/ 86 Sr ( i ) by assuming that the rock compositions observed are products of a mixing of mantle‐derived magma and crustal contaminant. The Sr–Nd isotopic compositions of the regional Cambrian picrite in the Yongjing terrane (Y. Zhang et al, ) were used as the mantle‐derived end member, and the average compositions of the upper crust and lower crust (Goldstein & Jacobsen, ; Vervoort et al, ) were used as the possible crustal contaminants. Modelling results indicate that less than 10% crustal contaminants to the mantle‐derived magmas can yield Sr–Nd isotopic compositions of the Shangzhuang intrusion (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…540–510 Ma, the South Qilian ocean was opening and separated the Qaidam and the Qilian Blocks. Seamount/oceanic plateaus resulting from hot spots were constructed on the South Qilian ocean crust (Yan et al., ; Zhang, Song, et al., ). The initiation of southward subduction of the South Qilian oceanic crust led to the formation of intra‐oceanic arc (Fu, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Zircons with ages ranging from 775 to 520 Ma are consistent with the timing of the opening and spreading of the Qilian Ocean, which was part of the Proto‐Tethys Ocean (Song, Niu, Su, Zhang, et al, ; Song, Niu, Su, & Xia, ; Figure c). The spreading of the Qilian Ocean was accompanied by extensive volcanic activity in the NQOB, as reflected by the diabase swarms in the Liugouxia area, which date to 738–604 Ma (single‐grain zircon ages; Mao et al, ), the Zhulongguan basalts, which date to 600–580 Ma (SIMS U–Pb age; Xu et al, ), and the plume‐type ophiolite in the Lajishan area, which dates to 525 Ma (according to LA‐ICP‐MS U–Pb dating; Zhang et al, ). Moreover, ages falling in this range have also been identified from the Devonian strata of the NQOB (Xu et al, ), which indicates that the NQOB experienced strong extension‐related magmatism at that time (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Li, Li, et al () also proposed that the Qilian Ocean is part of the Proto‐Tethys Ocean during the Early Paleozoic. Given the results from river sediments (Kang, Chen, Li, Bao, & Zhang, ) and Lajishan plume‐type ophiolite (Zhang et al, ) found within the CQB, the CQB is considered to have been a palaeo‐oceanic plateau. Based on the study of river sediments, we find that the age groups and age spans in the CQB are similar to those in the NQOB (Kang et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%